The Philippine Congress, 1987-1992. (Ermita, Manila Creative Computech Pub., 1988)
This publication is a salute to the first Congress of the Republic after the EDSA Revolution and a salute to the new Philippine democracy as well. It contains a list of all congressmen/women per region, within the period stated. Pictures of these personalities, together with their achievements and some personal information are presented.
Keywords: Legislators -- Philippines -- Directories; Statemen -- Philippines -- Directories